Hypertonic Dextrose and Morrhuate Sodium Injections (Prolotherapy) for Lateral Epicondylosis (Tennis Elbow): Results of a Single-blind, Pilot-level Randomized Controlled Trial - Rabago, David (2013)
OBJECTIVE: Chronic lateral epicondylosis (CLE) is common, debilitating and often refractory. Prolotherapy (PrT) is an injection therapy for tendinopathy. The efficacy of two PrT solutions for CLE was evaluated. DESIGN: 3-arm randomized controlled trial. 26 adults (32 elbows) with ≥3 months of CLE were randomized to ultrasound-guided PrT with dextrose (PrT-D), PrT with dextrose-morrhuate (PrT-DM) or watchful waiting (Wait-and-see). The primary outcome was the Patient-Rated Tennis Elbow Evaluation (PRTEE; 100-points) at 4, 8 and 16 weeks, (all groups) and 32 weeks (PrT groups). Secondary outcomes included pain-free grip strength and magnetic resonance imaging (MRI) score. RESULTS: PrT-D and PrT-DM participants reported improved PRTEE composite and subscale scores at 4, 8 and/or 16 weeks compared to Wait-and-see (p<0.05). At 16 weeks, compared to baseline, PrT-D and PrT-DM groups improved composite PRTEE scores by 18.7±9.6 (41.1%) and 17.5±11.6 (53.5%) points, respectively. Grip strength of PrT-D participants exceeded that of PrT-DM and Wait-and-see at 8 and 16 weeks (p<0.05). There were no differences in MRI scores. Satisfaction was high; there were no adverse events. CONCLUSIONS: Prolotherapy resulted in safe, significant improvement of elbow pain and function compared to baseline status and wait-and-see control. This pilot study suggests the need for a definitive trial.